Health and Development - Borowy, Iris (2023)
Health and development require one another: there can be no development without a critical mass of people who are sufficiently healthy, and people cannot be healthy without societal developments. 11 case studies from 9 countries on 3 continents since the late 19th century show how different actors have struggled to reconcile the nature of health and development policies, and the subordination of these policies to a range of political objectives.